Tribological Behaviors of Porous 3D Graphene Lubricant Reinforced Monomer Casting Polyamide 6 Composite. Issue 5 (13th February 2020) - Wang, Liping; Pan, Bingli; Gao, Jiayu; Huang, Saisai; Xie, Mengxin; Li, Chunyan; Luo, Denglin; Liu, Jichun; Wang, Honggang
Abstract : A porous 3D graphene lubricant is designed using a polyurethane (PU) foam vehicle and a self‐lubricating composite is thereafter prepared by pouring monomer casting polyamide 6 (MCPA6) into the 3D graphene lubricant. The microstructure of the composite is studied using infrared (IR), thermogravimetric analysis (TGA), X‐ray diffractometer (XRD), and scanning electron microscopy (SEM). The results of tribological properties and mechanical properties show that the composite exhibits enhanced tribological behaviors while inheriting excellent mechanical properties of neat MCPA6; the wear resistance of the composite is over 160 times higher than that of neat MCPA6 (1.3 m s −1, 140 N). The friction and wear mechanism of the composite is determined. The designed porous 3D graphene composite shows the merits of the increased friction reduction and antiwear performances with decreased loading content of graphene. This research opens a new insight for designing 3D graphene composite in severe tribological conditions. Abstract : A porous 3D graphene composite with the merits of reducing the content of graphene dramatically and increasing the friction reduction and antiwear performances is designed and fabricated. This research opens a new insight for designing 3D graphene composite in severe tribological conditions.